2007
DOI: 10.1562/0031-8655(2001)0730064taeapa2.0.co2
|View full text |Cite
|
Sign up to set email alerts
|

Topically Applied Eicosapentaenoic Acid Protects Against Local Immunosuppression Induced by UVB Irradiation, cis-Urocanic Acid and Thymidine Dinucleotides¶

Abstract: UVB‐induced immunosuppression, a promoter of photocarcinogenesis, involves the formation of pyrimidine dimers and cis‐urocanic acid (cis‐UCA), but reactive oxygen species (ROS) also plays an important role. Eicosapentaenoic acid (EPA) can inhibit photocarcinogenesis, but due to its polyunsaturated nature it is susceptible to oxidative damage by ROS. The antioxidant defense system may therefore be challenged upon ultraviolet‐B (UVB) irradiation in the presence of EPA. We investigated whether topically applied E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…Our findings were consistent with supplementation studies in animals (14,31) and epidemiologic surveys (8,9) and highlighted a mechanism whereby n23 PUFA supplementation may act to reduce UVR-induced skin cancer risk in humans (32). This study was pertinent because traditional topical sunscreens are less effective at protecting against photoimmunosuppression than against UVR-induced erythema, as indicated by the sun protection factor (33), and they are generally applied inadequately, as well as infrequently, outside of vacation periods (34,35).…”
Section: Discussionsupporting
confidence: 83%
“…Our findings were consistent with supplementation studies in animals (14,31) and epidemiologic surveys (8,9) and highlighted a mechanism whereby n23 PUFA supplementation may act to reduce UVR-induced skin cancer risk in humans (32). This study was pertinent because traditional topical sunscreens are less effective at protecting against photoimmunosuppression than against UVR-induced erythema, as indicated by the sun protection factor (33), and they are generally applied inadequately, as well as infrequently, outside of vacation periods (34,35).…”
Section: Discussionsupporting
confidence: 83%
“…1). Consistently, Moison et al (21) have shown that topically applied EPA protected against immune suppression, but increased doses of EPA resulted in decreased vitamin C and glutathione levels after UVB irradiation. These results indicate that maintaining an adequate antioxidant defense system is important for the protective effects of PUFA against UVB irradiation.…”
Section: Discussionmentioning
confidence: 65%
“…The residues of the undecomposed PD in group A or B penetrating into the dermis would probably be insufficient to inhibit phospho‐ERK1/2 MAPK as opposed to PD in group C, which exerted a reversible role against local UVB‐induced immuno‐suppression. Thus, besides vitamins E and C (33), eicosapentaenoic acid (32) and caffeic acid (42), the ERK1/2‐specific inhibitor PD or its analogues might be used potentially against UVB‐induced immunosuppression.…”
Section: Discussionmentioning
confidence: 99%
“…In our system, previous studies have suggested the protocols of the mouse model of UVB‐induced local immunosuppression (32–36), and the key point on the dose of UVB ranges from 8 to 15 kJ/m 2 (32–34, 37). Thus, different doses of UVB (6, 8, 10, 12, 14 and 16 kJ/m 2 ) were used for irradiation on the depilated abdominal skin in UVB‐tested groups, for an appropriate dose of UVB to induce local immunosuppression in our system.…”
Section: Methodsmentioning
confidence: 99%